The Effect of the Renewed Concept Strategy on Second-Grade Intermediate Students' Achievement in Spelling (Journal of the College of Basic Education, 2026)
The current research aims to investigate the impact of the renewed concept strategy on the achievement of second-grade middle school students in dictation. To achieve this goal, the researcher formulated a null hypothesis: "There is no statistically significant difference at a significance level of (0.05) between the average scores of students in the experimental group who study dictation using the renewed concept strategy and the average scores of students in the control group who study the same subject using the traditional method in the post-achievement test." The researcher adopted the experimental approach, and the research sample consisted of 68 second-grade middle school students at Al-Farabi Intermediate School in Baghdad, affiliated with the Baghdad First Rusafa Education Directorate, North Baghdad Education Department. They were randomly selected, with 34 students from the experimental group and 34 students from the control group. The researcher conducted statistical equivalence between the students in the two research groups on the following variables: (students' ages calculated in months and parents' academic achievement). The researcher prepared an achievement test consisting of 14 paragraphs. The researcher used the statistical package SPSS. The results of the research reached by the researcher were: "There is a statistically significant difference between the two groups, as the experimental group outperformed the control group in the post-test." The researcher recommended the need to guide Arabic language teachers to employ modern educational methods in educational situations, and the need to include them in training courses on the use of various teaching methods. The researcher also suggested conducting studies on the impact of the renewed concept strategy on other branches of the Arabic language.